(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2008)
The banquet canopy, erected by Ptolomaeus II in the Alexandrian palaces, is described by Athenaeus of Naukratis (in a text newly translated here), writing at the end of the 2nd century A.D., on the base of the account of Callixeinos Rhodios, who probably lived in the last decades of the 3rd century B.C.; in his turn, he would have relied on documents of the royal archives, i.e. reports and, hypothetically, figurative evidence.The structure, likely built on the occasion of the first Ptolemaia in 279-278 B.C., was meant for a limited number of guests: court dignitaries, but especially ambassadors from all the oikoumene and probably the seventy Jewish translators – the aim was a cultural encyclopaedism and a worldwide policy. The marquee is analysed in parallel with the procession, intended instead for the Greek population of Alexandria and of the chora, and suggests to place, tentatively, the stadion where the procession took place, not too far from the palaces. The pavilion, maybe related with Sostratus of Cnydos, the designer of the Lighthouse and the inventor of the two-level porticoes, is, ideologically, the final expression of the Persian canopies and of Alexander’s tent at Susa; nevertheless, the study of the apadanas and of the Greek hypostyle halls shows the typological and functional independence of the Ptolemaic tent from these buildings, often mentioned as its models.